Self-directed learning readiness among web-based learners / Shireen Haron - Haron, Shireen (Institute of Research, Development and Commercialization (IRDC), 2007)
The purpose ofthis research is to explore the practice of self-directed learning in web-based learning environments. The main objectives ofresearch are: (I) to determine whether students following UNITAR and UiTM web-based learning models are ready as self-directed learners, (2) to establish the relationship between level of readiness to students' academic achievement. The research employed the quantitative methodology. Data were collected using the Self-Directed Learning Readiness Scale (SDLRS). SDLRS is developed and designed to measure the level of readiness for self-directed learning among adult learners. The data set comprised of 109 students responding to the SDLRS instrument. From the 109 students, 53 students are from UNITAR and 56 students arefrom UiTM.